(untitled) (Revista Peruana de Investigación Educativa, 2023)
The article shows the meanings of pertinence and relevance, as criteria of educational quality, of four types of educational actors in two indigenous primary schools in the Sierra de Zongolica, Veracruz, Mexico. Likewise, the tensions produced by these meanings are analyzed at two levels: the tension between opposing notions of relevance of each actor and the tension generated by prioritizing relevance over relevance. Both criteria refer to subjective and contextual aspects of quality; relevance from the global and relevance from the local. Its integration is crucial to encompass both curricular and community learning. An ethnographic approach in two schools with supervisors, technical-pedagogical advisers, teachers, students, mothers - which favored in-depth interviews, observation and drawings-interviews - allowed the construction of qualitative data on these meanings and tensions and their analysis. through grounded theory. The results show that the notions of relevance of boys, girls and mothers are far from the dominant notions of relevance in the indigenous educational policy and place the need for a relevant education that expands and complicates areas of importance to the communities, such as the dimension environmental. The absence of spaces for reflection between the community and the educational authorities on the aims of education makes it difficult to reconcile the different meanings, which in turn promotes notions of quality situated as a result of the reflection of each school community.